Surgical treatment of congenital umbilical hernia in a Siamese cat - Riwu, Katty Hendriana Priscilia; Kholik, Kholik; Safitri, Indi Yulia (ARSHI Veterinary Letters, 2024)
A hernia involves the protrusion of abdominal visceral organs through an opening into a sac composed of the peritoneum, tunica flava, and skin. An umbilical hernia refers explicitly to protrusion of the abdominal viscera at the umbilicus. This case study aims to enhance skills in diagnosing and treating congenital umbilical hernias in a Siamese cat patient. Based on historical and clinical findings, the Siamese cat was diagnosed with an umbilical hernia. Treatment involved an abdominal laparotomy to reposition the hernia contents back into the abdominal cavity. Post-surgery, the cat was treated with the antibiotic amoxicillin and the anti-inflammatory drug dexamethasone (Glucortin®). The surgical wound healed by the eighth day after surgery.